Contraception and the obese woman - Reifsnider, Elizabeth (J Am Assoc Nurse Pract, 2013)
PURPOSE: Obesity has reached epidemic rates among U.S. women of reproductive age, many of whom want to use contraception. However, some forms of contraception can have adverse effects on an obese woman's health. This article explores risks of contraception available in the United States and provides clinical recommendations for use by obese women. DATA SOURCES: Information was compiled by reviewing the scientific literature on contraception and female obesity using CINAHL, MEDLINE, PubMed search engines. CONCLUSIONS: The evidence is largely supportive of combined oral contraceptive (COC) use in carefully screened obese women without known risks factors for cardiovascular disease. The efficacy of COCs may be slightly reduced in obese women because of increased body mass. Other types of hormonal contraceptives have varying safety and efficacy reports when used by obese women. Intrauterine devices do not have reduced efficacy nor increased risks for obese women but insertion may be more difficult. Obesity has no effect on efficacy of barrier methods of contraception. IMPLICATIONS: Clinicians should conduct a careful history and physical exam with selected supporting laboratory tests when considering prescription of hormonal contraceptives for obese women. Obese women require health counseling to carefully follow directions for contraceptive use to avoid unintended pregnancy.